The utilization and impact of adjuvant therapy following neoadjuvant therapy and resection of pancreatic adenocarcinoma: does more really matter?. Issue 11 (November 2020) - Drake, Justin A.; Stiles, Zachary E.; Behrman, Stephen W.; Glazer, Evan S.; Deneve, Jeremiah L.; Somer, Bradley G.; Vanderwalde, Noam A.; Dickson, Paxton V.
Abstract: Background: Although neoadjuvant therapy is increasingly administered to patients with pancreatic ductal adenocarcinoma (PDAC), the impact of additional adjuvant therapy (AT) following resection is not well defined. Methods: The National Cancer Database (NCDB) was queried for patients who received neoadjuvant therapy followed by R0 or R1 resection for PDAC. Factors influencing survival, including the receipt of AT were evaluated. Results: Of patients receiving neoadjuvant therapy and resection 680 (33.8%) received AT and 1331 (66.2%) did not. For R0 resected patients ( n  = 1800), lymphovascular invasion (HR 1.24, p  = 0.034) and increasing N classification (N1: HR 1.27, p  = 0.019; N2: HR 1.51, p  = 0.004) were associated with increased risk of death while AT was not associated with improved overall survival (OS) (HR 0.88, p  = 0.179). Following R1 resection ( n  = 211), AT was associated with reduced risk of death (HR 0.57, p  = 0.038). Within propensity matched cohorts, median OS for patients receiving and not receiving AT was 32.1 and 30.0 months after R0 resection ( p  = 0.184), and 23.6 and 20.5 months after R1 resection ( p  = 0.005). Conclusion: This analysis demonstrated that AT did not yield OS benefit for patients who had neoadjuvant therapy and R0 resection and a statistically significant, although relatively short, improvement in OS for patients who underwent R1 resection.